Effectiveness of multimedia Digital Video Disk on knowledge gain of improved dairy farming practices - Meena, B S; Kumar, Ranjith; Singh, Amit (Indian Journal of Dairy Science, 2014)
Livestock sector plays a multi-faceted role in socio-economic development of rural households. Empirical evidences indicate that livestock is an important component of the agriculture system, providing an additional source of income, nutritional cover and act a liquid asset to poor families. With the advancement of agriculture and livestock sector information and knowledge had increasingly become an important factor of production for effective decision-making. Information communication Technology (ICT) services have wide potential to uplift the economy of livestock holders and among various communication media available, the emerging cos effective educational DVD appears to hold great promise. Keeping these in view the present study was planned to identify perceived need of IDFPs and to assess the effectiveness of developed DVD module in IDFPs. The present study was conducted in six randomly selected villages of Krishnagiri district of Tamil Nadu. Ninety dairy farmers were investigated for identifying perceived need and to assess the effectiveness of DVD based information module. The result indicated that majority of respondent had medium level of perceived needs on breeding, feeding, health care and management. The perceived need index of each practices state that respondents were having highest need in health care i.e.61.78 per cent followed by animal breeding (57.65%) practices. The overall Knowledge gain through educational DVD on IDFPs was 14.21 per cent and maximum gain was observed in health care (16.62%). Thus the developed educational DVD was effective in terms of knowledge gain. Majority of the respondents were ‘satisfied ‘ regarding usefulness in enhancing knowledge (65.00%), suitability of the information to the field situation (72.22%), improves self-confidence (77.78%), arousal of curiosity and interest (62.22%), relevancy and appropriateness of the content (78.89%).